Lexical – Semantic Grouping Of The Verbs Of English And Uzbek Languages - Professor Muratova Manzura Islamovna (Peerian Journals Publishing, 2025)
This article investigates the features of linguistic unites in the modern linguistics, their semantic field, thematic and lexical – semantic grouping which is discussed in the works of world scientists.
Keywords: semantic field; thematic grouping; lexical; semantic grouping